Cross-University Mobility of University Teaching Staff in Russia - Olga Gorelova (Voprosy obrazovaniya / Educational Studies Moscow, 2016)
We investigate into cross-university academic mobility, which implies working for more than one university over a teaching career. Judging by available research results, mobility affects positively the academic system as a whole, although its correlation with personal teacher characteristics differs from country to country. According to the Changing Academic Profession survey conducted using the same methodology in 19 countries of the world in 2007–2009 and in Russia in 2012, we analyze the correlation of cross-university academic mobility with publication activity, working time distribution and professional communication of the academic staff. We demonstrate that the level of cross-university staff mobility was extremely low in the early 2010s, which was considered normal by the academic community though. Under such conditions, almost no significant correlations were found between mobility and professional activity characteristics of instructors (productivity, time distribution and collaboration with colleagues), the latter being more or less the same for both mobile and non-mobile staff members.